Applicability of indocyanine green fluorescence tracing with subserosal dye injection in laparoscopic lymph node dissection for gastric cancer: a preliminary study - Zhangwei Yang; Pengwei Wang; Dandan Bao; Yi-Ren Hu; Senrui Chen; Yi Huang; Pingting Li (Videosurgery and Other Miniinvasive Techniques)
Introduction: Gastric cancer is a common malignancy of the digestive system, primarily metastasizing to the lymph nodes. Adequate lymph node dissection is crucial for accurate staging and improving patient prognosis. However, the complex distribution of lymph nodes around the stomach poses a significant challenge for thorough dissection.